Where's my entourage? The curious case of 2-oleoylglycerol, 2-linolenoylglycerol, and 2-palmitoylglycerol. (August 2016) - Murataeva, Natalia; Dhopeshwarkar, Amey; Yin, Danielle; Mitjavila, José; Bradshaw, Heather; Straiker, Alex; Mackie, Ken
Graphical abstract: Abstract: 2-Arachidonoylglycerol (2-AG) is the most abundant endogenous cannabinoid in the brain and an agonist at two cannabinoid receptors (CB1 and CB2 ). The synthesis, degradation and signaling of 2-AG have been investigated in detail but its relationship to other endogenous monoacylglycerols has not been fully explored. Three congeners that have been isolated from the CNS are 2-linoleoylglycerol (2-LG), 2-oleoylglycerol (2-OG), and 2-palmitoylglycerol (2-PG). These lipids do not orthosterically bind to cannabinoid receptors but are reported to potentiate the activity of 2-AG, possibly through inhibition of 2-AG degradation. This phenomenon has been dubbed the 'entourage effect' and has been proposed to regulate synaptic activity of 2-AG. To clarify the activity of these congeners of 2-AG we tested them in neuronal and cell-based signaling assays. The signaling profile for these compounds is inconsistent with an entourage effect. None of the compounds inhibited neurotransmission via CB1 in autaptic neurons. Interestingly, each failed to potentiate 2-AG-mediated depolarization-induced suppression of excitation (DSE), behaving instead as antagonists. Examining other signaling pathways we found that 2-OG interferes with agonist-induced CB1 internalization while 2-PG modestly internalizes CB1 receptors. However in tests of pERK, cAMP and arrestin recruitment, none of the acylglycerols altered CB1 signaling. Our results suggest 1) that these compounds do not serve as entourage compounds under the conditions examined, and 2) that they may instead serve as functional antagonists. Our results suggest that the relationship between 2-AG and its congeners is more nuanced than previously appreciated.